2017
DOI: 10.1002/jcsm.12179
|View full text |Cite
|
Sign up to set email alerts
|

Tissue sodium accumulation and peripheral insulin sensitivity in maintenance hemodialysis patients

Abstract: BackgroundRecent data suggest that sodium (Na+) is stored in the muscle and skin without commensurate water retention in maintenance hemodialysis (MHD) patients. In this study, we hypothesized that excessive Na+ accumulation would be associated with abnormalities in peripheral insulin action.MethodsEleven MHD patients and eight controls underwent hyperinsulinemic–euglycemic–euaminoacidemic clamp studies to measure glucose (GDR) and leucine disposal rates (LDR), as well as lower left leg 23Na magnetic resonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Kopp et al [20] observed that, despite comparable TBW assessed by BIS, ECV was higher in HD patients with type II diabetes mellitus as compared to non-diabetics, whereas intracellular volume was lower. Also, skin and muscle sodium content, assessed by 23 Na MRI, were higher in the diabetics. Of interest, ECV correlated with HbA1C in the diabetics.…”
Section: Non-cardiovascular Factors On Abnormalities In Fluid Statusmentioning
confidence: 86%
See 2 more Smart Citations
“…Kopp et al [20] observed that, despite comparable TBW assessed by BIS, ECV was higher in HD patients with type II diabetes mellitus as compared to non-diabetics, whereas intracellular volume was lower. Also, skin and muscle sodium content, assessed by 23 Na MRI, were higher in the diabetics. Of interest, ECV correlated with HbA1C in the diabetics.…”
Section: Non-cardiovascular Factors On Abnormalities In Fluid Statusmentioning
confidence: 86%
“…It has been shown that using 23 Na MRI that HD is able to mobilize skin as well as muscle sodium [20], although the efficacy may be dependent upon local or systemic regulatory mechanisms, as evidenced by the inverse relation between skin sodium and vascular endothelial growth factor levels [16,21]. At first glance, the nonosmotic storage of sodium would seem to be a beneficial adaptation mechanism to buffer extremes in sodium intake.…”
Section: Non-osmotic Sodium Storagementioning
confidence: 99%
See 1 more Smart Citation
“…A study by Brands and colleagues showed that such Na + -retaining effects may be limited to uncontrolled Type II diabetes [32]. In 11 maintenance haemodialysis patients, higher muscle sodium content was, in a similar way, associated with insulin resistance [34]. Furthermore, in the soleus muscle of salt-sensitive hypertensive Dahl rats, the RAAS was shown to activate the NF-κB pro-inflammatory pathway, inducing moderate hyperinsulinemia and insulin resistance [33].…”
Section: Na + Homeostasis and Hyperinsulinismmentioning
confidence: 99%
“…71,92 Furthermore, tissue sodium accumulation was shown recently to be associated with muscle structural and functional disturbances contributing to peripheral insulin resistance. 93 Tissue sodium accumulation has been observed in a number of degenerative or inflammatory pathologies that are associated with poor outcomes. [94][95][96] For example, tissue sodium and water content has been explored in a model of acute muscle atrophy obtained by unloading the calf muscles of 1 leg.…”
mentioning
confidence: 99%